Automation of Filling Cryogenic Vessels with Perlite - Štěrba, Jan; Černohlávková, Valérie; Soukup, Josef (Manufacturing Technology Journal, 2015)
Liquefied technical gases are used in almost all sectors, regardless of whether this is industrial application (engineering, food processing, electronics), as well as in health and other sectors. These gases are kept in cryogenic vessels. A cryogenic vessel is a two-walled vessel where the inner vessel is used to keep the gas, the outer vessel is used as packaging, and the space between the inner and outer vessels is thermally insulated. The insulation must have such parameters to ensure that the stored cryogenic gases remain in the liquefied state for the longest possible time. Various materials and methods are used to insulate the vessels, but the most common insulation for cryogenic vessels is perlite insulation in combination with vacuum. The problems of isolation of cryogenic vessels using perlite are dealt with by only a few specialized companies that produce vessels for liquefied technical (cryogenic) gases.
Keywords: cryogenic vessels; perlite; vacuum; cryogenic technical gases